Critical Thinking Dimensions Among Nursing Students Across Educational Levels: A Cross-Sectional Study - Gita Adelia; Esperanza Zuriguel Pérez; Imelda Rahmayunia Kartika; Eka Malfasari; Arieny Rizafni (PT.Mantaya Idea Batara, 2026)
Background: Critical thinking is essential for nursing students to provide safe, evidence-based, and patient-centered care. Methods: This cross-sectional study described and compared critical thinking abilities among students in the Diploma III (D-3), Bachelor of Nursing (S-1), and Professional Nursing (Ners) programs at Institut Kesehatan Payung Negeri Pekanbaru. Of 521 eligible students, 493 participated, resulting in a 94.6% response rate. Data were collected using the N-CT-4 Students questionnaire and analyzed with the Kruskal–Wallis and Pearson’s chi-square tests. Result: Nearly half of the students (49.7%) demonstrated a moderate level of critical thinking. The educational program was not significantly associated with the critical thinking category, χ²(4) = 8.288, p = 0.082, Cramer’s V = 0.092. No significant differences were found across programs in the personal (p = 0.104), intellectual and cognitive (p = 0.408), interpersonal and self- management (p = 0.620), or technical dimensions (p = 0.673), with negligible effect sizes (rank ε² = 0.0016–0.0092). Conclusion: suggest that the three programs had similar critical thinking profiles at the time of measurement. Longitudinal studies using objective assessments are recommended to evaluate the development of critical thinking throughout nursing education.